PERFORMANCE ANALYSIS OF WEB-BASED RELATIVE AND PRECISE POINT POSITIONING TECHNIQUES WITH DIFFERENT SATELLITE VISIBILITY CONDITIONS - Albayrak, Müge; Erdoğan, Bahattin; Erkaya, Halil (Boletim de Ciências Geodésicas, 2020)
The Global Navigation Satellite System (GNSS) is used for precise positioning applications, such as surveying and geodesy. The aim of the present work is to evaluate the effectiveness of web-based relative positioning (RP) and precise point positioning (PPP) GNSS post-processing services using measurements of different satellite visibility obstacles. Within this framework, static GNSS observations were conducted at three control benchmarks selected taking the impact of natural and human-made obstacles on satellite signals into consideration. 3 hours of static GNSS observations in Istanbul, Turkey were repeatedly obtained from three control BMs over six days and were evaluated through two RP (AUSPOS, OPUS) and three PPP (CSRS-PPP, Magic-PPP, GAPS-PPP) web-based GNSS post-processing services. The 6-day average of the three control benchmark coordinates computed using the Bernese GPS software v5.0, and were accepted as true results. They were compared to the local coordinates acquired through the RP and PPP web-based GNSS post-processing services. The different satellite visibility conditions were found to have significant effects on the GNSS point positioning solutions. We also found that web-based GNSS post-processing services provide easy and effective solutions for geodetic positioning applications.